METHOD OF CALCULATION OF MICROWAVE STEP FILTERS ON COMBINED LINE SEGMENTS - Karpukov, L. M.; Korolkov, R. Y. (Radio Electronics, Computer Science, Control, 2024)
The matrix method of calculation step microwave filters is offered. The method is based on use of matrixes of the special kind made of polynoms of complex frequency, corresponding a denominator and numerators of parameters of dispersion of the filter. Results of calculation of filters with as much as possible-flat and equal wave characteristics of attenuation are presented.